Workplace dignity amongst clinical nurses - Jennifer de Beer; Hawazen Rawas; Wadea Beheri (BMC, 2024)
Abstract Background The workplace environment plays a pivotal role in employees' lives as they spend many hours there. Recently, greater attention has been placed on workplace conditions as a key social determinant of health. One way through which workplace conditions may affect health is workplace dignity. This study aimed to describe clinical nurses' workplace dignity. Methods The study design was descriptive and cross-sectional. Clinical nurses within a tertiary institution were randomly sampled. Data collection included the Workplace Dignity scale which is an 18 item-seven-point Likert scale consisting of dignity and indignity questions (α.98, and 0.95, respectively). Data collection commenced with a pilot followed by a final data collection phase. Ethical considerations were included via informed consent, anonymity, and confidentiality. Data analysis included means, standard deviations, and Pearson correlations. Results The pilot test yielded a reliability coefficient - α 0.93. Two hundred and thirty-six clinical nurses participated in the study resulting in a response rate of 87.4%. The average mean age of participants was 37.966 ± 0.635 (min 25- max 60) years. Most participants were female (92.8%) with a Bachelor of Science in Nursing Degree (77.5%). The overall mean experience as a registered nurse was 16.038 ± 0.589 years. Nationality responses were divided into Saudi (41.5%) and non-Saudi (58.5%). The construct of general dignity had the highest mean score of 5.52 (SD 1.46), with question 14: "I have dignity at work" having the highest overall mean score of 5.63 (SD 1.4). There was a positive correlation and statistical significance with a 'p < 0.000 i.e. as a nurses' experience as a registered nurse increased, workplace dignity scores increased. Conclusion The findings of this study indicated that inherent value and general dignity were the highest-scored constructs while indignity and respectful interaction scored the lowest. This study allows for reflection on the importance of workplace dignity, as an impactful and important organizational phenomenon that affects either positively or negatively on employee well-being and performance, hence workplace dignity must be prioritized within work environmental infrastructures.